Multimodalność w literackich narracjach zombiecentrycznych: - - Olkusz, Ksenia (Zagadnienia Rodzajów Literackich, 2019)
The article focuses on the analysis of the concept of multimodality in the context of zombiecentric stories. The article attempts to indicate the variety of narrative techniques in works a priori perceived as belonging to a lower aesthetic category due to their common (though unfounded) inclusion in the horror genre. Various aspects of multimodality, expressed in the visual dimension (e.g. typographic or illustrative) or in the use of focalization, were subjected to close analysis. These aesthetic procedures are employed not only to depart from the cliché plot schemas of zombie pandemic, but are also used for worldbuilding as tools enabling construction of credible and deeply immersive communications. The high creative competence of the authors of zombie-centric narratives attests to the research potential these texts have to offer.